Al-Hassan bin Muhammad al-Sagani - Pir Muhammad Hassan; Abdul Majid Nadeem (بازیافت)
Al-Hassan bin Muhammad al-Sagani was distinguished Islamic scholar of medieval times. He is little known to Urdu world.In his remarkable book Albab, he investigated the vocabulary and  documented some rare sources, and distinguished what was in the language dictionaries from the hadith, and in this approach he is not imitating one of the authors of the compilations that were written before him, but He reviewed their collections and relied on the most authentic narratives, choosing the sayings of trusted masters, citing the names of the Arab horses and their swords, their spots and their lands, their lightning and their circuits, their knights and their poets, citing the poems on health. This article is an Urdu translation of his introduction written by Peer Muhammad Hasan.